Intravital Imaging of Adoptive T-Cell Morphology, Mobility and Trafficking Following Immune Checkpoint Inhibition in a Mouse Melanoma Model - Lau, Doreen; Garçon, Fabien; Chandra, Anita; Lechermann, Laura M.; Aloj, Luigi; Chilvers, Edwin R.; Corrie, Pippa G.; Okkenhaug, Klaus; Gallagher, Ferdia A. (Frontiers in Immunology, 2020)
Efficient T-cell targeting, infiltration and activation within tumors is crucial for successful adoptive T-cell therapy. Intravital microscopy is a powerful tool for the visualization of T-cell behavior within tumors, as well as spatial and temporal heterogeneity in response to immunotherapy. Here we describe an experimental approach for intravital imaging of adoptive T-cell morphology, mobility and trafficking in a skin-flap tumor model, following immune modulation with immune checkpoint inhibitors (ICIs) targeting PD-L1 and CTLA-4. A syngeneic model of ovalbumin and mCherry-expressing amelanotic mouse melanoma was used in conjunction with adoptively transferred OT-1+ cytotoxic T-cells expressing GFP to image antigen-specific T-cell behavior within the live tumor microenvironment. Dynamic image analysis of T-cell motility showed distinct CD8+ T-cell migration patterns and morpho-dynamics within different tumor compartments in response to ICIs: this approach was used to cluster T-cell behavior into four groups based on velocity and meandering index. The results showed that most T-cells within the tumor periphery demonstrated Lévy-like trajectories, consistent with tumor cell searching strategies. T-cells adjacent to tumor cells had reduced velocity and appeared to probe the local environment, consistent with cell-cell interactions. An increased number of T-cells were detected following treatment, travelling at lower mean velocities than controls, and demonstrating reduced displacement consistent with target engagement. Histogram-based analysis of immunofluorescent images from harvested tumors showed that in the ICI-treated mice there was a higher density of CD31+ vessels compared to untreated controls and there was greater infiltration of T-cells towards the tumor core, consistent with increased cellular trafficking post-treatment.